Evaluasi Implementasi Keselamatan dan Kesehatan Kerja (K3) pada Proyek Pembangunan Ruang Kelas Baru SDN 004 Sangatta Utara - Fransiskus, Fransiskus; Anggitasari, Inge (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The implementation of Occupational Safety and Health (OSH) in construction projects is a crucial aspect to create a safe and healthy work environment. This study aims to evaluate the extent of OSH implementation and identify the barriers encountered during its application in the classroom construction project at SDN 004 Sangatta Utara. The method used is a quantitative descriptive approach, with data collected via questionnaires distributed to project workers. The data were then analyzed using mean scores, standard deviation, and interval interpretation. The results show that OSH implementation falls into the “good” category. The main obstacles in OSH implementation are the lack of training for workers and the limited availability of personal protective equipment (PPE).